Exploring the Effectiveness of Smart Technologies in the Management of Type 2 Diabetes Mellitus. (January 2018) - Coda, Andrea; Sculley, Dean; Santos, Derek; Girones, Xavier; Acharya, Shamasunder
The global epidemic of diabetes, with increasing prevalence of type 2 diabetes (T2D), is placing a huge burden on health care management and financial systems. Unless new strategic solutions are developed, the increasing prevalence of T2D will result in a significant rise in morbidity, health care costs, and complications associated with diabetes. The introduction of smart devices in diabetes management may provide meaningful improvements in clinical outcomes, patient engagement, as well as potential cost reductions for the health care system. Future research may be capable of providing new smart and interactive solutions to the growing multidisciplinary diabetes team and, most important, to reduce the morbidity associated with T2D.